2016
DOI: 10.1161/circulationaha.115.016686
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Diseases Following Childhood Cancer Treatment

Abstract: Survivors of childhood cancers treated with radiotherapy and anthracycline run a high dose-dependent risk of developing CD. CDs develop earlier in patients treated with anthracycline than in those treated without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 26 publications
3
57
1
5
Order By: Relevance
“…Thirdly, studies on cardiac biomarkers regarding other relevant cancer therapy‐related side effects such as an increased risk for coronary artery disease or other forms of cardiotoxic cancer therapy such as radiotherapy were not available for the present analysis. Patients who received high‐dose anthracyclines and chest radiotherapy have an up to 61.5‐fold increased risk and a cumulative incidence for overall cardiac disease of 11.0% at the age of 40 years . Therefore, evaluation of cardiac biomarkers in the detection of cardiovascular adverse events other than heart failure is needed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, studies on cardiac biomarkers regarding other relevant cancer therapy‐related side effects such as an increased risk for coronary artery disease or other forms of cardiotoxic cancer therapy such as radiotherapy were not available for the present analysis. Patients who received high‐dose anthracyclines and chest radiotherapy have an up to 61.5‐fold increased risk and a cumulative incidence for overall cardiac disease of 11.0% at the age of 40 years . Therefore, evaluation of cardiac biomarkers in the detection of cardiovascular adverse events other than heart failure is needed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mulrooney et al reported health outcomes in a cohort of just over 14,000 survivors of childhood and adolescent cancer and found that this population was at substantial risk for cardiovascular disease, with a two-to six-fold increased relative risk for coronary events in patients who had received >15 Gy to the heart compared to non-irradiated survivors [157]. Moreover, the relative risk of cardiovascular events was reported up to 60-fold higher in childhood cancer survivors that received a higher cardiac mean dose of >30 Gy compared to patients who received either no RT or a dose to the heart of 0.1 Gy or less [158]. While some studies report exposure at an older age may also be a risk factor for more severe normal tissue toxicity [159,160], a rodent study reported increased mortality rates and incidence of RT pneumonitis compared to geriatric rats after 13 Gy partial body irradiation [161].…”
Section: Preclinical Models To Study Cardiac Radiation Toxicities: Anmentioning
confidence: 98%
“…For instance, in a French cohort of 3162 childhood cancer survivors, in those patients who did not receive anthracyclines, at median follow-up of 26 years after estimated average doses to the heart ≥30 Gy, the risk of heart disease was increased several fold compared to patients who had received doses to the heart <0.1 Gy [11]. …”
Section: Cardiac Injury Of High-dose Radiationmentioning
confidence: 99%